2015
DOI: 10.1093/nar/gkv009
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific cleavage of dsRNA by Mini-III RNase

Abstract: Ribonucleases (RNases) play a critical role in RNA processing and degradation by hydrolyzing phosphodiester bonds (exo- or endonucleolytically). Many RNases that cut RNA internally exhibit substrate specificity, but their target sites are usually limited to one or a few specific nucleotides in single-stranded RNA and often in a context of a particular three-dimensional structure of the substrate. Thus far, no RNase counterparts of restriction enzymes have been identified which could cleave double-stranded RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Interestingly, mammalian RNase III class enzymes Dicer and Drosha, both implicated in the microRNA pathway, have been shown to exhibit specific base preferences at the cut site (44), which nevertheless do not match our motif. Further, no eukaryotic RNases with sequence specificity have been identified to date (45), whereas the unique case of RNase Mini-III from Bacillus subtilis that cleaves dsRNA in a sequence-specific manner was discovered recently (46). Clearly, more studies are required to elucidate the mechanism and to identify the responsible endonuclease(s), which also warrants research in other insects and organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mammalian RNase III class enzymes Dicer and Drosha, both implicated in the microRNA pathway, have been shown to exhibit specific base preferences at the cut site (44), which nevertheless do not match our motif. Further, no eukaryotic RNases with sequence specificity have been identified to date (45), whereas the unique case of RNase Mini-III from Bacillus subtilis that cleaves dsRNA in a sequence-specific manner was discovered recently (46). Clearly, more studies are required to elucidate the mechanism and to identify the responsible endonuclease(s), which also warrants research in other insects and organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report we showed that deletion of the α5b-α6 loop in BsMiniIII did not alter the binding of this enzyme to dsRNA with a preferred cleavage sequence17. We hypothesized that the α5b-α6 loop is involved in selecting the cleavage site and further posited that this selection occurred at the step of cleavage itself and did not involve selective binding.…”
Section: Resultsmentioning
confidence: 85%
“…The results of our previous study17 suggested that the α5b-α6 loop of BsMiniIII is involved in the recognition and selection of the target sequence in dsRNA. According to the structural model of the Mini-III-dsRNA complex, in addition to this loop, the α4 helix is also in close proximity to the sequence cleaved (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations